Lacquer and Imitation Lacquer Folding Screens in New Spain - Sonia I. Ocaña-Ruiz (Heritage, 2023)
Folding screens were very popular in New Spain beginning in the late 16th century. From the second half of the 17th century on, many Chinese and some European lacquer folding screens circulated in New Spain, inspiring the development of Novohispanic lacquer, imitation lacquer, and Chinese-style folding screens. The decorative technique of these Novohispanic folding screens has not been studied, but evidence suggests that some of them were made with techniques that have pre-Columbian roots, others with European lacquer techniques, and others still with paint and varnish adapted to produce a shiny surface resembling that of Asian lacquer. Thus, 18th-century New Spain was the place where there was the widest variety of lacquer folding screens in the world. Hitherto this variety has remained unnoticed, but studying it is essential to understand to what extent the globalization of the taste for lacquer gave rise to innovative solutions in the Americas.